Densities and heat capacities of the ammonia plus water plus NaOH and ammonia plus water plus KOH solutions - Salavera, D.; Libotean, S.; Patil, K. R.; Esteve, X.; Coronas, Alberto (Journal of Chemical and Engineering Data, 2006)
Ammonia + water + sodium hydroxide and ammonia + water + potassium hydroxide mixtures were chosen as potential candidates for absorption chillers driven by low-temperature heat sources. Heat capacity and density were studied between (293.15 and 353.15) K at a constant pressure of 1.8 MPa for these solutions using a heat flux Calvet-type calorimeter and a vibrating-tube densimeter, respectively. Measured data were well-correlated with temperature and composition using simple polynomial equations. The relative deviations between the experimental and calculated values in the density and heat capacity measurements were 0.20 % and 0.49 % for NH3 + H2O + NaOH solutions and 0.10 % and 0.36 % for NH3 + H2O + KOH solutions, respectively. Also, two density prediction methods were checked using the experimental data. Previously, it was necessary to measure the density of ammonia and hydroxide aqueous solutions in similar conditions. The results showed that both methods are suitable for predicting the density of these solutions.

Thermal conductivity measurement of polyglycol alkyl ethers at temperatures from (303.15 to 393.15) K - Salavera, Daniel; Patil, Kashinath R.; Coronas, Alberto (Journal of Chemical and Engineering Data, 2010)
Experimental Values of the thermal conductivity of five pure polyglycol alkyl ethers are presented in a temperature range from (303.15 to 393.15) K at a pressure of 1 MPa. Measurements were made with a Setaram C-80 II calorimetric device equipped with a suitable vessel Setup and ail auxiliary thermostat to measure at high-temperature conditions using the steady-state coaxial cylinders method. The measured values of the thermal conductivity were compared with data reported in the literature. The reliability and accuracy of the experimental method were confirmed with the measurements on pure benzene with well-known thermal conductivity values. Our data agreed with the limited data available in the literature and were correlated using an empirical expression. The Uncertainty of the results was estimated to be within 2.0 %, and the reproducibility of the data was better than +/- 0.5 %.

Reduced graphene oxide composite with oxidizable manganese/cobalt mixed oxide for p-cresol oxidation by using molecular oxygen - Jha, Ajay; Patil, Sagar H.; Solanki, Bhanu P.; Ribeiro, Ana P. C.; Castro, Carlos A. N.; Patil, Kashinath R.; Coronas, Alberto; Rode, Chandrashekhar V. (ChemPlusChem, 2015)
A composite of graphene oxide (GO) with mixed oxide (MnCo) was prepared by using a solvothermal method. During the synthesis, both the reduction of GO and growth of metal oxides took place simultaneously. The as-prepared composite material was highly selective for the liquid-phase oxidation of p-cresol to form p-hydroxybenzaldehyde in 71% yield within 1h. The composite material was characterised by SEM, X-ray photoelectron spectroscopy, high-resolution TEM and cyclic voltammetry (CV). A CV study revealed that the increase in the redox potential of the mixed oxide after being supported on GO, led to its higher activity of the catalyst for the oxidation reaction. The stability of the catalyst under the reaction conditions was studied by its successful reuse in three cycles.
Keywords: cyclic voltammetry; graphene; Oxidation; supported catalysts; transition metals

Influence of silver nanoparticles morphologies on density, viscosity and thermal conductivity of silver nanofluids and silver ionanofluids - Patil, Virendra Sudam; Andry, Cera-Manjarres; Salavera, Daniel; Rode, Chandrashekhar Vasant; Patil, Kashinath R; Coronas, Alberto (Journal of Nanofluids, 2018)
This paper explores the consequence of silver nanoparticles morphology (nanowires, nanoplates, and nanospheres) on density, viscosity and thermal conductivity of nanofluids and IoNanoFluids. Nuclear magnetic resonance spectroscopy results reveal that hydroxyl group in cation relates to silver nanoparticle surface of silver IoNanoFluid. Effect on bonding of silver nanoparticles after solvation in an ionic liquid was investigated with Infrared spectroscopy. UV-Visible spectroscopy analysis observed variations in color and optical properties of silver IoNanoFluids compared with nanofluids. Structural and morphological characterization of silver nanofluids and silver IoNanoFluids were carried out with Scanning electron microscopy and Transmission electron microscopy techniques. The presence of silver nanoparticles from the aqueous phase of nanofluids to viscous ionic liquid phase was confirmed by X-ray photoelectron spectroscopy and Energy dispersive analysis. The thermal stability study unveils that Choline bis(trifluromethylsulfonyl)imide ionic liquid, and its derived silver IoNanoFluids, are more stable than silver nanofluids. There was no considerable impact was observed for the silver nanoparticles morphology on the density of IoNanofluids. Moreover, two-dimensional silver structures raise the viscosity further compare to other two morphologies of silver nanoparticles in a base ionic liquid. Among all three studied morphologies, silver nanowires influence additional in the enhancement of thermal conductivity for silver nanofluids and IoNanoFluids. Enhanced thermal conductivity and reduced viscosity of silver nanowires based IoNanoFluid sorts this fluid as a potential heat transfer fluid.

Synthesis of silver nanoparticles colloids in imidazolium halide ionic liquids and their antibacterial activities for gram-positive and gram-negative bacteria - Patil, Virendra; Mahajan, Swapnil; Kulkarni, Mohan; Patil, Kashinath; Rode, Chandrashekhar; Coronas, Alberto; Yi, Gi-Ra (Chemosphere, 2020)
Four 1-butyl-3-methylimidazolium halide ionic liquids were synthesized via metathesis and anion exchange reactions. Silver nanoparticles (AgNPs) colloids were synthesized in four ionic liquids in the pressurized reactor by reduction of silver nitrate with hydrogen gas, without adding solvents or stabilizing agents. Antibacterial activities of base ionic liquids and AgNPs colloids in ionic liquids were reviewed by well-diffusion method for gram-positive Bacillus cereus (NCIM-2155) and gram-negative Escherichia coli (NCIM-2931) bacteria. Antibacterial activities of ionic liquids and AgNPs colloids in ionic liquids were observed to be controlled by ionic liquids anions and AgNPs particle size. The 1 -butyl-3-methylimidazolium iodide ionic liquid exhibited higher antibacterial activities among the studied ionic liquids. Further, the presence of AgNPs in 1-butyl-3-methylimidazolium iodide, ionic liquid enhanced its antibacterial activity for Bacillus cereus and Escherichia coli bacteria. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Anion effect; antibacterial activity; Imidazolium halides; ionic liquids; silver nanoparticles